Speech production after glossectomy: Methodological aspects. (April 2014) - Acher, Audrey; Perrier, Pascal; Savariaux, Christophe; Fougeron, Cecile
Abstract This article focuses on methodological issues related to quantitative assessments of speech quality after glossectomy. Acoustic and articulatory data were collected for 8 consonants from two patients. The acoustic analysis is based on spectral moments and the Klatt VOT. Lingual movements are recorded with ultrasound without calibration. The variations of acoustic and articulatory parameters across pre- and post-surgery conditions are analyzed in the light of perceptual evaluations of the stimuli. A parameter is considered to be relevant if its variation is congruent with perceptual ratings. The most relevant acoustic parameters are the skewness and the Center of Gravity. The Klatt VOT explains differences that could not be explained by spectral parameters. The SNTS ultrasound parameter provides information to describe impairments not accounted for by acoustical parameters. These results suggest that the combination of articulatory, perceptual and acoustic data provides comprehensive complementary information for a quantitative assessment of speech after glossectomy.